Evaluation of subclasses for T4‐classified squamous cell carcinoma of the external auditory canal. Issue 8 (13th May 2022) - Nabuurs, Cindy H.; Kievit, Wietske; Leemans, C. René; Smit, Conrad F. G. M.; van den Brekel, Michiel W. M.; Pauw, Robert J.; van der Laan, Bernard F. A. M.; Jansen, Jeroen C.; Lacko, Martin; Braunius, Weibel W.; Dai, Chunfu; Shi, Xunbei; et al.
Abstract: Background: T4‐classified squamous cell carcinoma (SCC) of external auditory canal (EAC) can potentially involve different anatomical structures, which could translate into different treatment strategies and survival outcomes within one classification. Our aim is to evaluate the clinical added value of T4‐subclasses proposed by Lavieille and by Zanoletti. Methods: Retrospective data, including patients with primary operated cT4‐classified EAC SCC, was obtained from 12 international hospitals. We subclassified according to the T4‐subclasses. The treatment strategies, disease‐free survival (DFS) and overall survival per subclass were calculated. Results: A total of 130 T4‐classified EAC SCC were included. We found commonly used treatment strategies per subclass according to Lavieille and the DFS seems also to differ per subclass. Subclass according to Zanoletti showed comparable treatment strategies and survival outcomes per subclass. Conclusion: Our study suggests that the subclass according Lavieille might have added value in clinical practice to improve care of T4‐classified EAC SCC.